Perancangan Iklan Poster Digital “STOP BULLYING” Berbasis Instagram @fisipunsri - Adam, Ryan (Inter Komunika, 2023)
Abstract. Cases of bullying are still common in Indonesia. This case is not only found in elementary schools, but also occurs in university. The increase in cases of bullying continues to increase every year. Starting from verbal bullying to bullying with physical violence. This causes the victim has an  experience psychological traumatize, even having the desire to commit suicide. One of the efforts to prevent this from happening again is to make a public service advertisement using a digital poster "Stop Bullying" which is then uploaded to social media Instagram. The method used in this study is a qualitative method using audience segmentation which includes demographics, geography, psychographics, and behavior. The data collection method used in this research is using primary and secondary data. The 5W+1H method is also used in solving problems in analyzing data. The theory used in this study is the hypodermic needle theory. The results of this study indicate that the "Stop Bullying" digital advertising design is designed using a creative concept consisting of typography, color, message content, and verbal messages which then the digital poster design will be uploaded via the @fisipunsri Instagram feed and story which is expected to be able to provide an appeal and preventing and stopping acts of bullying that are increasingly rampant, especially in the university.